The truth of human love. Facing the document of the Spanish Episcopal Conference - Caamaño López, José Manuel (Razón y fe, 2018)
This article aims to present a recent document from the Spanish Episcopal Conference entitled The truth of human love. Orientations on conjugal love, gender ideology and family legislation. For this, its basic contents will be exposed with a special look at its frontal criticisms of the distortion of love and sexuality caused by gender ideology (especially the theories of qeer and cyborg) and its influence on current legislation regarding life, marriage and family.